2014
DOI: 10.1242/jcs.134502
|View full text |Cite
|
Sign up to set email alerts
|

The formation of proximal and distal definitive endoderm populations in culture requires p38 MAPK activity

Abstract: BSTRACTEndoderm formation in the mammal is a complex process with two lineages forming during the first weeks of development, the primitive (or extraembryonic) endoderm, which is specified in the blastocyst, and the definitive endoderm that forms later, at gastrulation, as one of the germ layers of the embryo proper. Fate mapping evidence suggests that the definitive endoderm arises as two waves, which potentially reflect two distinct cell populations. Early primitive ectoderm-like (EPL) cell differentiation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 109 publications
1
7
0
Order By: Relevance
“…Our antibody microarray analyses indicated that cells treated with a combination of RA plus AC expressed members of the p38/MAPK and PI3K/AKT pathways in a differential manner as compared to cells treated with RA only, which suggests their involvement on the induction of ES to endodermal differentiation by RARβ2. This idea is consistent with reports describing the involvement of the p38 and PI3K cell signaling pathways on the commitment of endodermal lineages either during embryonic carcinoma or ES cell differentiation in culture (Smedberg et al, 2002; Villegas et al, 2013; Yap et al, 2014; also, see Binetruy et al, 2007 for a review). Thus, our findings provide evidence of a role played by the p38 and PI3K cell signaling pathways during the RA-induced differentiation of mouse ES cells along an endodermal lineage.…”
Section: Discussionsupporting
confidence: 91%
“…Our antibody microarray analyses indicated that cells treated with a combination of RA plus AC expressed members of the p38/MAPK and PI3K/AKT pathways in a differential manner as compared to cells treated with RA only, which suggests their involvement on the induction of ES to endodermal differentiation by RARβ2. This idea is consistent with reports describing the involvement of the p38 and PI3K cell signaling pathways on the commitment of endodermal lineages either during embryonic carcinoma or ES cell differentiation in culture (Smedberg et al, 2002; Villegas et al, 2013; Yap et al, 2014; also, see Binetruy et al, 2007 for a review). Thus, our findings provide evidence of a role played by the p38 and PI3K cell signaling pathways during the RA-induced differentiation of mouse ES cells along an endodermal lineage.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, previous work conducted using a specific small chemical compound inhibitor of p38α/Mapk14 and p38β/Mapk11 (herein referred to together as p38-Mapk14/11) has demonstrated eight- to 16-cell arrest phenotypes, associated with defects in embryo compaction, filamentous actin formation and glucose uptake, or compromised blastocyst formation typified by failures in appropriate blastocoel formation (for example, associated with tight-junction failure and reduced aquaporin expression), depending upon the exact timing of drug administration relative to the onset of embryo compaction [ 31 34 ]. A very recent study has also implicated a role for active p38-Mapk signalling in blastocyst TE formation via mediating autocrine Fgf2/Fgfr2-based signalling [ 19 ], and interesting evidence from experiments investigating the molecular regulators of canonical Wnt3a-signalling, using the mouse F9 teratocarcinoma cell model, suggests a potential role for p38-Mapks in regulating PrE formation [ 35 ]; indeed, the formation of definitive endoderm at gastrulation is known to require p38-Mapk activity [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The p38 MAPK signaling pathway is involved in many cellular processes, including inflammation and cell differentiation, survival and death. During embryonic development, the p38 inhibitor SB203580 blocks both mesoderm and endoderm differentiation from the primitive streak [ 15 ][ 18 ]. We have shown that SB203580 treatment inhibits mRNA expression of the primitive streak markers Wnt3 and Brachyury T but induces premature expression of neurogenesis markers, implicating p38 MAPK in the initial stages of primitive streak formation in the EB system.…”
Section: Discussionmentioning
confidence: 99%